204 Predictors of Spinal Fusion Within 2 Years of Posterior Fossa Decompression in Patients With Chiari Malformation Type 1 and Scoliosis: A Multi-Institutional Experience With the Park-Reeves Syringomyelia Research Consortium. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Monk, Steve H; Zhao, Shilin; Strahle, Jennifer; Averill, Christine; Couture, Daniel E; Johnston, James M; Kelly, Michael P; Torner, James; Park, Tae S; Limbrick, David D; Bonfield, Christopher M; Shannon, Chevis N
Abstract: INTRODUCTION: Approximately half of patients with scoliosis in the setting of Chiari malformation type 1 (CM-I) ultimately require deformity correction despite posterior fossa decompression (PFD). Using a multi-institutional prospective registry of patients diagnosed with CM-I and syringomyelia, this study aimed to evaluate risk factors impacting the need for corrective scoliosis surgery post-PFD. METHODS: We conducted a retrospective review of patients prospectively enrolled in the Park-Reeves Syringomyelia Research Consortium registry. Patients with at least 2 yr of follow-up data were included in our cohort. Descriptive statistics and multivariate regression were conducted using R. Statistical significance was set a priori at P < .05. RESULTS: Forty-five (29.8%) patients required spinal fusion after PFD (mean time to fusion: 18.4 ± 14.9 mo). Univariate analysis revealed that older age at scoliosis diagnosis (12.7 ± 3.1 mo vs 9.9 ± 3.9 mo, P < .001), age greater than or equal to 10 yr at scoliosis diagnosis (84% vs 50%, P < .001), history of spinal dysraphism (11% vs 2%, P = .014), greater preoperative scoliosis curve (46.9 ± 17.3° vs 25.5 ± 12.0°, P < .001), and preoperative scoliosis curve greater than or equal to 35° (76% vs 19%, P < .001) were associated with a need for spinal fusion. Clival canal angle was greater in the fusion group but not associated with a need for spinal fusion (147.8 ± 12.4° vs 143.8 ± 11.3°, P = .068). Multivariate regression revealed that older age at scoliosis diagnosis and greater preoperative curve were independently associated with a need for spinal fusion. CONCLUSION: Spinal fusion was necessary in only 30% of our patient cohort. Older age at scoliosis diagnosis and greater preoperative scoliosis curve were independent predictors of the need for spinal fusion within 2 yr post-PFD. Long-term follow-up data are needed to assess the effectiveness of spinal fusion post-PFD.